Cryptocurrency price discrepancies under uncertainty: Evidence from COVID-19 and lockdown nexus. (June 2022) - Chen, Meichen; Qin, Cong; Zhang, Xiaoyu
Highlights: Bitcoin price discrepancies are larger under COVID-19 pandemic and lockdown nexus; Bitcoin plays a role of "alternative investment" under uncertainty; Rampant panic emotion explains the Bitcoin price discrepancies under uncertainty; Domestic capital control, sanitary policy stringency and cultural heterogeneity can moderate the general effect. Abstract: The past decades have witnessed recurrent price discrepancies in cryptocurrency markets across countries. In addition to prior explanations that generally attribute this phenomenon to domestic capital controls during normal periods, we provide another explanation that investors perceive cryptocurrency as an alternative (hedging) investment, especially under uncertainty. Using the emerging of the COVID-19 pandemic in 2020 and the subsequent lockdown policies implemented by a group of countries as natural experiments, we adopt a difference-in-difference framework to examine how the nexus affects Bitcoin price discrepancies. We find that price discrepancies are larger in countries with confirmed cases of COVID-19 and rigorously implementing lockdown policies. We then verify our "alternative investment" hypothesis on the mechanism by showing that countries with intensified exposure to media hype on COVID-19 topics and with more panic emotion among citizens during the pandemic generally experienced larger Bitcoin price discrepancies than their counterparts. We also find that domestic capital control, sanitary policy stringency, uncertainty aversion, individualistic culture, and governmental power could moderate the general effect.